2020
DOI: 10.1039/d0ta01059f
|View full text |Cite
|
Sign up to set email alerts
|

Embedding molecular photosensitizers and catalysts in nanoporous block copolymer membranes for visible-light driven hydrogen evolution

Abstract: The integration of molecular photosensitizers and catalysts into functional soft matter supports holds great promise for future energy conversion technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
40
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 52 publications
2
40
1
5
Order By: Relevance
“…In a recent study, a related heterogeneous thiomolybdate-polymer catalyst was reported, revealing hydrogen evolution of 0.5 μmol H 2 mg À1 polymer. [41] The comparison shows that the systems reported here show significantly better performance, even though the catalyst loading in the present study is lower compared with the literature report.…”
Section: Catalytic Activitycontrasting
confidence: 47%
“…In a recent study, a related heterogeneous thiomolybdate-polymer catalyst was reported, revealing hydrogen evolution of 0.5 μmol H 2 mg À1 polymer. [41] The comparison shows that the systems reported here show significantly better performance, even though the catalyst loading in the present study is lower compared with the literature report.…”
Section: Catalytic Activitycontrasting
confidence: 47%
“…[76][77][78] Recently, the electrostatic immobilization of molybdenum sulphide [Mo 3 S 13 ] 2À as HER catalyst and the photosensitizer [Ru(bpy) 3 ] 2+ on the surface of nanoporous block copolymer membranes has been reported. 79 An assembly of chromophores and reaction centres in three dimensions can be achieved by incorporation of these functionalities in metal organic frameworks (MOFs). 80,81 This short overview on systems for artificial photosynthesis illustrates the tremendous variety of available and investigated material systems.…”
Section: Introductionmentioning
confidence: 99%
“…16 This finding prompted the search for molecular 17 or nanoparticulate forms 18 of these materials, with the aim to maximize the number of exposed active species. The [Mo3S13] 2 molecular clusters have been established as one of such promising co-catalysts for dark electrocatalytic 16,[19][20][21][22] and photocatalytic HER under heterogeneous [23][24][25] and homogeneous conditions. 26,27 Anchoring of the cluster onto various solid catalyst supports or light absorbers is straightforward and has been demonstrated for TiO2, 28 carbon materials, 20,21 and recently also for polymeric carbon nitride-based material.…”
Section: Introductionmentioning
confidence: 99%